2020
DOI: 10.1192/j.eurpsy.2020.100
|View full text |Cite
|
Sign up to set email alerts
|

Educational attainment inequalities in depressive symptoms in more than 100,000 individuals in Europe

Abstract: Background Increasing educational attainment (EA) could decrease the occurrence of depression. We investigated the relationship between EA and depressive symptoms in older individuals across four European regions. Methods We studied 108,315 Europeans (54% women, median age 63 years old) from the Survey on Health, Ageing and Retirement in Europe assessing EA (seven educational levels based on International Standard Classification of Education [ISCED] classification) and depressive symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
5
18
1
Order By: Relevance
“…The most important finding of our study is that anxiety levels are related to patient education level. Large-scale survey studies have associated higher education levels with lower long-term depression or anxiety [7,8], but our study produced results to the contrary, and Demir et al [9] also found a positive correlation between education level and stress in patients with chronic orthopedic disease. We believe the explanation for this phenomenon is that when highly educated people have a health problem, their anxiety level may be higher in relation to their awareness.…”
Section: Discussioncontrasting
confidence: 76%
“…The most important finding of our study is that anxiety levels are related to patient education level. Large-scale survey studies have associated higher education levels with lower long-term depression or anxiety [7,8], but our study produced results to the contrary, and Demir et al [9] also found a positive correlation between education level and stress in patients with chronic orthopedic disease. We believe the explanation for this phenomenon is that when highly educated people have a health problem, their anxiety level may be higher in relation to their awareness.…”
Section: Discussioncontrasting
confidence: 76%
“…To simplify analysis, the original six ISCED groups were reduced and dichotomized into 'basic education' for those with ISCED levels 1 to 3 and 'higher education' for levels 4 to 6. The approach of grouping ISCED was adapted from other publications [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies that were conducted were not related to these three variables together, rather they were all separately studied. Although some of the foreign studies have shown that these three variables have a significant interaction with each other (20,34), we need to investigate this interaction among Malaysian adult as we have different culture and sociodemographic characteristics.…”
Section: Association Of Socio-demographic Factors With Mental Illness...mentioning
confidence: 99%